Rancang Bangun Aplikasi Layanan Pengaduan Masyarakat Pada Dinas Kependudukan Dan Pencatatan Sipil Kabupaten Dompu Berbasis Web - Julianingsih; Esabella, Shinta (Buletin Ilmiah Informatika Teknologi, 2025)
The Population and Civil Registration Office (DUKCAPIL) of Dompu Regency is a service that is responsible for carrying out administrative affairs in the field of population and civil registration, covering all services and complaints related to the community, such as the implementation of population registration services. The utilization of digital technology at the Population and Civil Registration Office of Dompu Regency is still manual, especially regarding complaints. This research aims to design a community complaint service application at the Population and Civil Registration Office of Dompu Regency using the waterfall method. It aims to produce a web-based application with an attractive appearance and features. login feature, dashboard, complaint feature, service feature and manage services and reporting feature. The data collection methods used are observation, interviews, and literature study. This application is built using the waterfall software development methodology and object modeling, Laravel framework, and PHP programming language, with black box testing. The result of this research is a web-based community complaint service application at the Population and Civil Registration Office of Dompu Regency. It is expected that this application can facilitate more efficient community complaint services at the Population and Civil Registration Office of Dompu Regency.